Association of angiotensin-converting enzyme G2350A gene polymorphisms with hypertension among patients with intracerebral haemorrhage. Issue 3 (June 2019) - Imran, Imran; Syahrul, Syahrul; Sofia, Sofia; Farida, Farida; Musadir, Nasrul; Fajar, Jonny K.
الملخص: أهداف البحث: لتقييم علاقة الإنزيم المحول للأنجيوتنسين المتعدد الأشكال الجينية مع ارتفاع ضغط الدم، وحجم الورم الدموي داخل المخ، ومستوى الوعي، ونتيجة المرض بين المرضى المصابين بنزف داخل المخ. طرق البحث: أجريت دراسة مقطعية عرضية في مستشفى زين العابدين العام خلال الفترة من مايو ٢٠١٦ إلى يونيو ٢٠١٧. استخدم تفاعل البلمرة المتسلسل للحصول على التركيب الوراثي للإنزيم المحول للأنجيوتنسين المتعدد الأشكال الجينية. كما تم تقييم حجم الورم الدموي داخل المخ باستخدام صيغة تقدير الحجم. وتم تقييم مستوى الوعي بواسطة مقياس جلاسجو للغيبوبة. وتقييم نتيجة المرض باستخدام مقياس جلاسجو للنتائج. وتحليل اختبار العلاقة للتركيب الوراثي مع حالة ارتفاع ضغط الدم، وحجم الورم الدموي داخل المخ، ومقياس جلاسجو للغيبوبة، ومقياس جلاسجو للنتائج للحالات المصابة بنزف داخل المخ باستخدام الانحدار اللوجستي المتعدد. النتائج: تضمنت الدراسة ما مجموعه ٧٥ مريضا بنزف داخل المخ. من هؤلاء، ٥٩ مريضا مصابا بارتفاع ضغط الدم، و٢٤ مريضا لديه حجم الورم الدموي داخل المخ ≥ ٦٠ سنتيمترا مكعبا، و١٦ مريضا لديه مقياس جلاسجو للغيبوبة ≤ ٨، و٧٢ مريضا لديه مقياس جلاسجو للنتائج ١-٣. أظهرت نتائجنا أن الجين للإنزيم المحول للأنجيوتنسين المتعدد الأشكال الجينية كان مرتبطا بشكل كبير بازدياد ارتفاع ضغط الدم ب ٣.٦ مرة، ولكن ليس مع حجم الورم الدموي داخل المخ، ومستوى الوعي، ونتيجة المرض بين المرضى المصابين بنزف داخل المخ. الاستنتاجات: الجين للإنزيم المحول للأنجيوتنسين المتعدد الأشكال الجينية يرتبط بارتفاع ضغط الدم عند المرضى المصابين بنزف داخل المخ. Abstract: Objectives: To evaluate the correlation of angiotensin-converting enzyme (ACE) G2350A gene polymorphisms with hypertension, brain hematoma volume (BHV), level of consciousness, and disease outcome among intracerebral haemorrhage (ICH) patients. Methods: A cross-sectional study was conducted in Zainoel Abidin General Hospital from May 2016 to June 2017. Polymerase chain reaction was used to genotype ACE G2350A gene polymorphisms. BHV was assessed using the ABC/2 volume estimation formula. Level of consciousness was assessed by Glasgow coma scale (GCS). Disease outcome was assessed using Glasgow outcome scale (GOS). Association tests for ACE G2350A genotype in the context of hypertension status, BHV, GCS score, and GOS score in subjects with ICH was analysed by multiple logistic regression. Results: A total of 75 ICH patients were included in the study. Of those, 59 patients exhibited hypertension, 24 patients had BHV ≥60 cm 3, 16 patients possessed GCS scores ≤8, and 72 patients had GOS scores of 1–3. Our analysis determined that the A allele of the ACE G2350A gene polymorphism was significantly associated with a 3.6-fold increase in hypertension; however, this polymorphism was not associated with BHV, level of consciousness, and disease outcome among ICH patients. Conclusion: The A allele of the ACE G2350A gene polymorphisms is associated with hypertension among ICH patients.